A novel alum-sludge based Constructed Wetland system to reduce pollution effects of agricultural run-off: first results. (28th September 2007) - Babatunde, A.O.; Zhao, Y.Q.
This paper is a research brief highlighting the development of a novel alum-sludge based Constructed Wetland (CW) system aimed at reducing the pollution effects of agricultural run-offs. Alum sludge is a by-product of drinking water treatment plants where aluminium sulphate is used as coagulant. The alum sludge cakes were used as the main support matrix in the constructed wetland system, having been shown to have a greater capacity to retain contaminants, especially phosphorus, through sorption phenomena, ionic exchange and other physico-chemical processes. The dewatered alum-sludge cakes used proved beneficial in enhancing and sustaining phosphorus removal in the system, and the removal of organics is thought to be enhanced by the tidal flow mechanism employed. Overall removal of 82.3 ? 3.5% (BOD5) and 85.5 ? 2.1% (COD) was achieved in the system.